Evaluation of Competition Conditions in the Hotel Sector in Istanbul - ÖZER, Kazım Ozan; SALDAMLI, Asım (International Review of Management and Marketing, 2015)
The various dimensions of the concept of the competitiveness in service sectors have drawn attention of many researchers. Discipline of business concerns firm, sector and the international dimensions of national level competition. This study focus on explaining the competitiveness of Istanbul Hotel Sector by considering the dynamics connected to the sectoral competitiveness of Tourism. For the analysis, different data collection techniques have been used. As for the secondary data, literature review has been done about Michael Porter’s Five Forces Model that is mostly prefered for this kind of researches. For the primary data, senior managers of hotels in Istanbul Hotel Sector were applied to the interviews and formal interviews. As a result of this study it’s seen that Istanbul Hotel Sector has profitability rates that attract new entrants and the competition conditions are available for new entrants to the Istanbul Hotel Sector. Keywords: Industry Analyze; Hotel Sector; Competition JEL Classifications: M1; M2